Compositional response of Amazon forests to climate change (2018)
Most of the planet's diversity is concentrated in the tropics, which includes manyregions undergoing rapid climate change. Yet, while climate‐induced biodiversitychanges are widely documented elsewhere, few studies have addressed this issuefor lowland tropical ecosystems. Here we investigate whether the floristic and func-tional composition of intact lowland Amazonian forests have been changing by eval-uating records from 106 long‐term inventory plots spanning 30 years. We analysethree traits that have been hypothesized to respond to different environmental dri-vers (increase in moisture stress and atmospheric CO2concentrations): maximumtree size, biogeographic water‐deficit affiliation and wood density. Tree communitieshave become increasingly dominated by large‐statured taxa, but to date there hasbeen no detectable change in mean wood density or water deficit affiliation at thecommunity level, despite most forest plots having experienced an intensification ofthe dry season. However, among newly recruited trees, dry‐affiliated genera havebecome more abundant, while the mortality of wet‐affiliated genera has increasedin those plots where the dry season has intensified most. Thus, a slow shift to amore dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to signifi-cantly impact whole‐community composition. The Amazon observational record sug-gests that the increase in atmospheric CO2is driving a shift within treecommunities to large‐statured species and that climate changes to date will impactforest composition, but long generation times of tropical trees mean that biodiver-sity change is lagging behind climate change.KEYWORDSbioclimatic niches, climate change, compositional shifts, functional traits, temporal trends,tropical forests